2009
DOI: 10.1111/j.1468-3148.2008.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Action Plan, Staff Training, Management Support and Monitoring on Restraint Use and Costs of Work‐Related Injuries

Abstract: Background Dignity and respect are at the foundation of good care and effective treatment planning and are guiding service principles. The use of physical restraints is contrary to treatment with dignity and respect. Because of the numerous risks to clients and employees associated with the use of physical restraints, an innovative plan was implemented to minimize the use. Method Information was gathered to obtain a clear understanding of the employees' feelings about the initiative to minimize physical restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 0 publications
0
48
0
1
Order By: Relevance
“…The components outlined in this article, in light of other similar projects (Sanders, 2009), demonstrate the utility of behavior incident analysis for designing comprehensive clinical safety programs, reducing injuries to staff, and creating safer habilitation and living environments. Clearly, more research in this area is needed to identify effective procedures that can be adopted by HSOs.…”
Section: Discussionmentioning
confidence: 97%
“…The components outlined in this article, in light of other similar projects (Sanders, 2009), demonstrate the utility of behavior incident analysis for designing comprehensive clinical safety programs, reducing injuries to staff, and creating safer habilitation and living environments. Clearly, more research in this area is needed to identify effective procedures that can be adopted by HSOs.…”
Section: Discussionmentioning
confidence: 97%
“…The change process helped Grafton leadership manage organizational behaviors through a clearly defined intervention that has been fine tuned up to and beyond the initial results provided by Sanders (2009). The ability to change a culture with so many unknowns and with the potential for dangerous outcomes shows that this method of change can work in extreme situations.…”
Section: Discussionmentioning
confidence: 99%
“…In the original study, Sanders (2009) reported results from a region of Grafton which included children (average census of 75 between the ages of 6 and 22) and adults (average census of 43 at ages 22 and older) with Bvarying levels of autism and/or intellectual disabilities along with concurrent psychiatric conditions and significant behavioral challenges^(p. 216). This represented outcomes for one of Grafton's regional operations.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations